Monocyte and Neutrophil Isolation, Migration, and Phagocytosis Assays. (3rd July 2018) - Maini, Alexander; Foote, Juliet R.; Hayhoe, Richard; Patel, Amit A.; O'Brien, Alastair; Avraham‐Davidi, Inbal; Yona, Simon
Abstract: This article describes methods for isolating mouse monocytes and neutrophils, as well as in vitro protocols for measuring cell phagocytosis, migration, and polarization. The method employed here for the isolation of naive phagocytes overcomes many of the difficulties previously encountered concerning phagocyte activation. Three in vitro protocols are provided for the analysis of cell migration, one requiring no specialized equipment, one requiring a modified Boyden chamber, and the other employing a flow chamber, which measures cell adhesion, rolling, and migration. Three in vitro protocols to examine phagocytosis have been included in this updated version. Finally, a method is provided for imaging polarized cells by confocal microscopy. © 2018 by John Wiley & Sons, Inc.